2014
DOI: 10.1002/ejic.201402103
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Cytotoxic Activity of AuI N,S‐Heterocyclic Carbenes Derived from Peptides Containing L‐Thiazolylalanine

Abstract: Thiazolium salts 2a-b derived from a dipeptide Boc-Gly-(Thz-Ala)-OMe (1b) containing the nonproteinogenic amino acid L-thiazolylalanine (Thz-Ala) can be used to generate the corresponding N,S-heterocyclic carbene (NSHC) gold(I) (3ab) and silver(I) (4) complexes. Reaction of the NSHC-gold(I) iodide 3b with Boc-Cys-Gly-OMe gives access to the peptide bioconjugate 5, which contains a NSHC-Au-(S-Cys) unit. Compounds 3-5 constitute the first coin metal NSHC-peptide complexes. All new compounds were comprehensively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 88 publications
1
23
0
Order By: Relevance
“…The cytotoxicity of complex 4 (IC50=26±2 μ m after 24 h, 38±2 μ m after 48 h and 41±2 μ m after 72 h) is higher than for the positive control cisplatin. This result is consistent with previously disclosed studies for water‐soluble gold(I) phosphane complexes, which reported IC50 values between 1 μ m and 100 μ m , depending on the cell line, incubation time, ligand type and lipophilicity of the gold(I) complexes …”
Section: Resultssupporting
confidence: 93%
“…The cytotoxicity of complex 4 (IC50=26±2 μ m after 24 h, 38±2 μ m after 48 h and 41±2 μ m after 72 h) is higher than for the positive control cisplatin. This result is consistent with previously disclosed studies for water‐soluble gold(I) phosphane complexes, which reported IC50 values between 1 μ m and 100 μ m , depending on the cell line, incubation time, ligand type and lipophilicity of the gold(I) complexes …”
Section: Resultssupporting
confidence: 93%
“…In addition, a number of gold conjugates derived from amino acids or peptides have been reported. As examples, N‐heterocyclic carbene (NHC)–gold complexes,, conjugates of ferrocene coordinated to gold(I) derivatives, gold(III) dithiocarbamates,, gold(I) azides, and gold(I) thiolates, with only one example of a chloro–gold–phosphane found in the recent literature.…”
Section: Introductionmentioning
confidence: 99%
“…Two gold(I) complexes 50 and 51 with N,S-heterocyclic carbenes derived from the peptides containing l-thiazolylalanine (Thz-Ala) showed good cytotoxic activity in vitro against the A549, MiaPaca2 and Jurkat cell lines (Figure 4a and Table 3) [25]. The carbene complex 50 with iodide was more efficient in all tested cell lines in respect to the thiolate-containing complex 51, what can be the consequence of the higher lability of Au-I bond in respect to the Au-S bond and higher lipophilicity of 50.…”
Section: Cell Line A549 Miapaca2 Jurkat Complexmentioning
confidence: 99%